Infertility and cortisol: a systematic review - Karunyam, Bheena Vyshali; Abdul Karim, Abdul Kadir; Mohamed, Isa Naina; Ugusman, Azizah; Mohamed, Wael Mohamed Yousef; Mohd Faizal, Ahmad; Abu, Muhammad Azrai; Kumar, Jaya (Frontiers Media S.A., 2023)
Introduction: Stress and infertility form a complex relationship. In line with this, various stress-related biological markers have been investigated in infertility.